Are Women Human? Tampon Taxes and the Semiotics of Exclusion - Spivack, Carla (Columbia Journal of Gender and Law, 2021)
By now, there is a robust body of scholarship critiquing the taxation of menstrual products from material, expressive, constitutional, and human rights perspectives. This literature highlights the issue of access to sanitary products in prisons, in secondary schools, and in poor countries. Invoking the expressive function of law, scholars have noted how the tax signals to women that their basic physical and health needs are not human necessities that merit tax exemption—like say Viagra—but are rather luxuries that should be taxed—like cigarettes and alcohol. In this tax regime, human needs considered basic enough to merit tax relief—thinning hair, for example—are male needs. So what else is new? As Catherine Mackinnon asked, ironically, decades ago: Are women human? In this Article, I want to turn the expressive critique of tampon taxation in the direction of semiotics. Culture constitutes systems of signs through which we understand our world. These signs convey meaning though their difference from other signs, not through any intrinsic meaning. Tax law has its own signs. By imposing differing tax regimes on people and things, it tells us how to read them. For example, through differing taxation, it tells us what a family is (one organized around a formal marriage) and is not (networks of dependence organized around cohabitants), what work is (labor exchanged for goods) and is not (housework), etc. Taxes also tell us which goods are luxuries and which are necessities by imposing a luxury tax on certain items and exempting others.